Animal Characters : Nonhuman Beings in Early Modern Literature - Boehrer, Bruce Thomas (Haney Foundation series., 2010)
"In Animal Characters Bruce Thomas Boehrer follows five species---the horse, the parrot, the cat, the turkey, and the sheep---through their appearances in an eclectic mix of texts, from romances and poetry to cookbooks and natural histories. He shows how dramatic changes in animal character types between 1400 and 1700 relate to the emerging economy and culture of the European Renaissance. In early modern European culture, animals not only served humans as sources of labor, companionship, clothing, and food; these nonhuman creatures helped to form an understanding of personhood. Incorporating readings of Shakespeare's plays, Milton's Paradise Lost, Margaret Cavendish's Blazing World, and other works, Boehrer's series of animal character studies illuminates a fascinating period of change in interspecies relationships"--BOOK JACKET.